2014
DOI: 10.1590/1678-476620141044413417
|View full text |Cite
|
Sign up to set email alerts
|

Aging and growth parameter from the Piaractus mesopotamicus (pacu) from the Cuiabá river, Mato Grosso, Brazil

Abstract: ABSTRACT. This study has aims to determine the age and to estimate the growth parameters using scales of the species. Individuals of Piaractus mesopotamicus (Holmberg, 1887) used in this study were captured in the commercial fishery conducted in the region, along the year 2006. The model selected to express the growth of the species was the von Bertalanffy Sl= Sl∞* [1-exp -k(t-to) ]. To determine if scales are suitable for studying the growth of pacu, we analyzed the relation between standard length (Sl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The maximum age of individual P. mesopotamicus was 5 years. Vaz (2001) found a similar age structure (5 years) based in scales readers, and Ambrósio et al (2014) observed the maximum of seven growth rings in the scales. Based on this study and previous (Vaz, 2001;Ambrósio et al, 2014) the estimative from maximum age indicates a short life cycle for P. Mesopotamicus.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…The maximum age of individual P. mesopotamicus was 5 years. Vaz (2001) found a similar age structure (5 years) based in scales readers, and Ambrósio et al (2014) observed the maximum of seven growth rings in the scales. Based on this study and previous (Vaz, 2001;Ambrósio et al, 2014) the estimative from maximum age indicates a short life cycle for P. Mesopotamicus.…”
Section: Discussionmentioning
confidence: 67%
“…The best model showed individual and sex effect on growth parameters. The sex effect in fish species, with females being larger than males or vice versa (Rljnsdorp, Ibelings, 1989;Imsland et al, 1997;Ambrósio et al, 2014) is not rare to detect. The difference in body length between males and females is related to variation in growth parameters (Morita et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations